2022
DOI: 10.3390/bioengineering9040135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jump-Rope-Specific Footwear Selection on Lower Extremity Biomechanics

Abstract: Footwear is among the most important equipment in sports to decrease injuries and enhance performance during exercise. In this study, we investigated differences in lower extremity plantar pressure and muscle activations during jump rope activities. Ten participants performed jump rope under two landing conditions with different footwear. A force platform (AMTI, 1000 Hz), a Novel Pedar-X system (Nove, 100 Hz), and a wireless electromyography (EMG) system (Noraxon, 1500 Hz) were used to measure biomechanical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…During the YBT, the VICON MX motion analysis system (Oxford, United Kingdom), with a sample rate of 100 Hz ( Tang et al, 2022 ) was used to record the maximum flexion angles of the ankle, knee, and hip joints. Surface electromyography (Noraxon, United States) with a sample rate of 1500 Hz ( Yu et al, 2022 ) was used to test the EMG signal characteristics of the TA and lateral GM. Recording the EMG signal from the beginning of the extension of the leg to the extension to the farthest.…”
Section: Methodsmentioning
confidence: 99%
“…During the YBT, the VICON MX motion analysis system (Oxford, United Kingdom), with a sample rate of 100 Hz ( Tang et al, 2022 ) was used to record the maximum flexion angles of the ankle, knee, and hip joints. Surface electromyography (Noraxon, United States) with a sample rate of 1500 Hz ( Yu et al, 2022 ) was used to test the EMG signal characteristics of the TA and lateral GM. Recording the EMG signal from the beginning of the extension of the leg to the extension to the farthest.…”
Section: Methodsmentioning
confidence: 99%
“…Footwear designed with a higher stiffness has been observed to alter the transmission ratio of the ankle joint during running, which in turn can enhance running performance [18,19]. Similarly, Yu et al [1,7] found that jump rope shoes with a low degree of toe uplift and a thin sole could significantly affect jump rope performance. Footwear that reduces plantar pressure may be more beneficial for long-term jump rope exercise [8].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanists have been studying ways to optimize sports equipment to improve athletic outcomes. This has led to a growing interest in understanding the biomechanics of jump rope movements and identifying factors that can positively impact performance [1,7,8]. There are various types of rope skipping, but they all involve continuous vertical jumps at a relatively low height.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the exact volume, the difference in volume between the genders, the variation in volume over the course of a day or sports activities would be beneficial for the manufacture of shoes [10,11,12,13]. Once again, the medical field could improve the management of footwear for different foot morphotypes or conditions such as Cavo varus feet, progressive collapsing foot deformity or hallux valgus [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%